ANALISIS PENGARUH EVIRONMENTAL PERFORMANCE, UKURAN PERUSAHAAN DAN GROWTH TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Nugraha, Muhammad Resky; Sri Mulyantini; Erna Hernawati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to examine empirically the effect of environmental performance firm size, firm growth, to corporate social responsibility (CSR) disclosure. The population in this study are the companies include in manufactur company listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The data used in this research are financial statements, annual reports, and PROPER. Sample selection was done by purposive sampling method and obtained 30 companies that fit the criteria. Hypothesis testing studies conducted by multiple data panel regression analysis by using Statistical Product and EVIEWS. The results showed that partially environmental performance has a significant effect on the Corporate Social Responsibility (CSR) disclosure, firm size has a no significant effect on the Corporate Social Responsibility (CSR) disclosure, while firm growth no significant effect on Corporate Social Responsibility (CSR) disclosure